2011
DOI: 10.1038/nsmb.2100
|View full text |Cite
|
Sign up to set email alerts
|

SUMOylation regulates telomere length homeostasis by targeting Cdc13

Abstract: Telomere length homeostasis is an important aspect of telomere biology. Here we show that SUMOylation limits telomere length and targets multiple telomere proteins in Saccharomyces cerevisiae. A main target is Cdc13, which both positively and negatively regulates telomerase and confers end protection. We demonstrate that Cdc13 SUMOylation restrains telomerase functions by promoting Cdc13 interaction with the telomerase inhibitor Stn1, without affecting end protection. Mutation of the Cdc13 SUMOylation site (cd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
110
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(118 citation statements)
references
References 59 publications
7
110
0
1
Order By: Relevance
“…(Fig. 5A) (21). Furthermore, mutations in Polα also cause telomere elongation in budding yeast (33), and CST interacts with the Polα-primase complex (34,35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Fig. 5A) (21). Furthermore, mutations in Polα also cause telomere elongation in budding yeast (33), and CST interacts with the Polα-primase complex (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Like the modification with ubiquitin (ubiquitylation) and other ubiquitin-like modifiers, SUMOylation is achieved with a distinct but evolutionarily conserved enzymatic cascade consisting of E1-activating, E2-conjugating, and E3 ligase enzymes (15)(16)(17). Factors involved in SUMOylation regulate recombinationbased telomere maintenance in mammals and budding yeast (18)(19)(20), and SUMOylation of Cdc13 promotes Cdc13-Stn1 interaction to restrain telomerase-dependent telomere elongation in budding yeast (21). In fission yeast, mutations of SUMO (Pmt3) or SUMO E3 ligase (Pli1) lead to long telomeres in a telomerase-dependent manner (22,23).…”
Section: Significancementioning
confidence: 99%
“…The phosphorylation of Cdc13 at T308 by Cdk1 in late S phase and G 2 favors the interaction of Cdc13 with Est1 rather than the competing interaction of Cdc13 with Stn1 -Ten1 (Li et al 2009). Another modification, Cdc13 SUMOylation, peaks in early to mid S phase (Hang et al 2011). Mutation of the SUMO site reduced the interaction with Stn1, promoting telomere elongation (Hang et al 2011).…”
Section: Telomere Replicationmentioning
confidence: 99%
“…Another modification, Cdc13 SUMOylation, peaks in early to mid S phase (Hang et al 2011). Mutation of the SUMO site reduced the interaction with Stn1, promoting telomere elongation (Hang et al 2011). Ku70/80 and Sir4 are other telomeric proteins modified by Siz2 E3 ligase-dependent SUMOylation, promoting perinuclear position of budding yeast telomeres (Ferreira et al 2011).…”
Section: Telomere Replicationmentioning
confidence: 99%
“…53 Interestingly, recent studies have found that prior to its phosphorylation, Cdc13 is target of SUMOylation. 54 SUMOylation of Cdc13 promotes its interaction with Stn1 and thereby restrains telomerase function, whereas mutation of the SUMOylation site in Cdc13 induces telomerase-mediated lengthening of telomeres due to weakening of the Cdc13-Stn1 interaction.…”
Section: Ubiquitylation and Telomere Dysfunctionmentioning
confidence: 99%